Characterization of interference thin films grown on stainless steel surface by alternate pulse current in a sulphochromic solution - Junqueira,Rosa Maria Rabelo (2008)
The aim of this work was to characterize thin interference films grown on the surface of AISI 304 stainless steel for decorative purposes. Films were grown in a sulphochromic solution at room temperature by an alternating pulse current method. The morphology and chemical state of the elements in the films were investigated by field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), glow discharge optical emission spectrometry (GDOES), and infrared Fourier transform spectroscopy (FTIR). Depth-sensing indentation (DSI) experiments and wear abrasion tests were employed to assess the mechanical resistance of the films. The coloration process resulted in porous thin films which increased the surface roughness of the substrate. The interference films mainly consisted of hydrated chromium oxide containing iron. Increasing film thickness produced different colors and affected the mechanical properties of the coating-substrate system. Thicker films, such as those producing gold and green colors, were softer but more abrasion resistant.